Corporate Governance Models and Practices in Japan and East Asia: Proceedings of a Panel Discussion - Aronson, Bruce E. (Columbia Journal of Asian Law, 2014)
Despite general interest in the economic rise of Asia and in the role of law in the development of the region, the literature on comparative corporate governance in Asia is surprisingly undeveloped with respect to in-depth comparisons among Asian countries. In particular, it should be both valuable and feasible to compare and contrast corporate governance systems and practices among countries in East Asia, in light of Japan’s historical influence and more recent divergences from that influence. At a recent conference sponsored by Waseda University, a distinguished group of corporate law scholars from Japan, Korea, Taiwan, and China engaged in a broad-ranging panel discussion centering on the question of the operation and reform of traditional stakeholder-oriented corporate governance systems featuring concentrated ownership and a board of directors involved in day-to- day management against the need to account for greater monitoring of management on behalf of shareholders. For example, the panelists agreed that the traditional internal corporate auditors (or kansayaku in Japanese) have not appeared to operate effectively in monitoring management, and to some extent they should be supplemented or replaced by outside directors. However, the scope and pace of such change varies considerably among countries in East Asia, and skepticism remains about the effectiveness of outside directors. The panel discussion highlighted both the challenges and significant potential rewards for greater scholarly collaboration in making cross-Asian comparisons in the field of corporate governance.